Safety and tolerability of the novel inhaled corticosteroid fluticasone furoate in combination with the β2 agonist vilanterol administered once daily for 52 weeks in patients ≥12 years old with asthma: a randomised trial. Issue 6 (25th February 2013) - Busse, William W; O'Byrne, Paul M; Bleecker, Eugene R; Lötvall, Jan; Woodcock, Ashley; Andersen, Leslie; Hicks, Wesley; Crawford, Jodie; Jacques, Loretta; Apoux, Ludovic; Bateman, Eric D
Abstract : Background: The inhaled corticosteroid fluticasone furoate (FF) in combination with the long-acting β2 agonist vilanterol (VI) is in development for asthma and chronic obstructive pulmonary disease. Objective: To assess the safety and tolerability of FF/VI over 52 weeks in patients with asthma. Methods: Patients (aged ≥12 years; on inhaled corticosteroid) were randomised (2:2:1) to FF/VI 100/25 µg or FF/VI 200/25 µg once daily in the evening, or fluticasone propionate (FP) 500 µg twice daily. Safety evaluations included adverse events (AEs), non-fasting glucose, potassium, 24-h urinary cortisol excretion, ophthalmic assessments, heart rate and pulse rate. Results: On-treatment AEs were similar across groups (FF/VI 66–69%; 73% FP). Oral candidiasis/oropharyngeal candidiasis was more common with FF/VI (6–7%) than FP (3%). Twelve serious AEs were reported; one (worsening hepatitis B on FP) was considered drug related. Statistically significant cortisol suppression was seen with FP compared with both FF/VI groups at Weeks 12 and 28 (ratios [95% CI] to FP ranged from 1.43 [1.11 to 1.84] to 1.67 [1.34 to 2.08]; p≤0.006), but not at Week 52 (ratios to FP were 1.05 [0.83 to 1.33] for FF/VI 100/25 µg and 1.09 [0.87 to 1.38] for FF/VI 200/25 µg). No clinically important changes in non-fasting glucose, potassium, QT interval corrected using Fridericia's formula (QTc[F]) or ophthalmic assessments were reported. Pulse rate (10 min post dose [Tmax ], Week 52) was significantly increased with FF/VI versus FP (3.4 bpm, 95% CI 1.3 to 5.6; p=0.002 [FF/VI 100/25 µg]; 3.4 bpm, 95% CI 1.2 to 5.6; p=0.003 [FF/VI 200/25 µg]). Mean heart rate (24-h Holter monitoring) decreased from screening values in all groups (0.2–1.1 bpm FF/VI vs 5 bpm FP; Week 52). Conclusions: FF/VI (100/25 µg or 200/25 µg) administered once daily over 52 weeks was well tolerated by patients aged ≥12 years with asthma. The overall safety profile of FF/VI did not reveal any findings of significant clinical concern. ClinicalTrials.gov: NCT01018186